Dominant inter-area oscillation mode identification using local measurement and modal energy for large-scale power systems with high grid-tied VSCs penetration. (May 2020) - Wang, Lixin; Cai, Guowei; Chen, Zhe; Yang, Deyou; Sun, Zhenglong; Wang, Bo; Xi, Yufei
Highlights: The dynamic interaction mechanism between the grid-tied VSCs and the AC power grid in the electromechanical bandwidth is revealed. A local measurement signal selection strategy for monitoring inter-area oscillations is proposed. A dominant inter-area oscillation mode extraction method based on modal energy is presented. The excellent effectiveness and adaptability performance of the local measurement signal selection strategy are verified by using IEEE 16-generator 5-area test system. Abstract: Appropriate phasor measurement unit (PMU) signals must be selected to monitor electromechanical oscillations for large-scale renewable energy connected power system. Considering the response mechanism of the active and reactive power of grid-tied voltage source converters (VSCs) in the electromechanical time scale, a local measurement signal selection strategy for monitoring inter-area oscillations (0.1–0.7 Hz) based on the inherent electromechanical characteristics of the synchronous generators (SGs) is proposed. Moreover, optimized dynamic mode decomposition (OpDMD) algorithm is used to extract dominant modal parameters (e.g., oscillation frequency, damping ratio, and mode shape). First, from the perspective of frequency response characteristics, the dynamic interaction mechanism between grid-tied VSCs and the AC grid is revealed in the electromechanical time scale. Second, considering the intrinsic relationship between the inherent inertia constant of the SG and observability of response after a disturbance, a local measurement signal selection strategy for monitoring the inter-area electromechanical oscillation of power systems with high grid-tied VSCs penetration is proposed. On the basis of the selected local measurement signals, the OpDMD algorithm identifies dominant inter-area oscillation parameters. Results of the IEEE 16-generator 5-area system show that the proposed method can accurately extract electromechanical modal parameters from the limited PMU measurements, verifying the effectiveness of the local measurement signal selection strategy for inter-area oscillation monitoring of power systems with high grid-tied VSCs penetration.